Introduction: Can we bridge the rigour-relevance gap? - FINCHAM, Robin (Institutional Knowledge at Singapore Management University, 2009)
The following series of articles emanate from a session held at the first Journal of Management Studies Conference on the theme of ‘Beyond knowledge management: advancing the organizational knowledge research agenda’. The conference was concerned to advance academic understanding of this broad topic and in addition to reflect on the role of management scholars as creators, commodifiers and disseminators of management and organizational knowledge. The latter theme arose from debates in relation to the apparent marginality of business school academics in the production of management knowledge (Barley et al., 1988; Gibson and Tesone, 2001; Spell, 2001) and their consequent (in)ability to develop and conduct research with practitioners and then communicate the results of this research to a practising audience. Drawing on Shapiro et al. (2007, p. 249), this broad debate can be framed as either a ‘knowledge transfer problem’ (what they term ‘lost in translation’) or a ‘knowledge production problem’ (what they ‘lost before translation’). In the former the solution is to produce publications and outlets that are designed to be attractive to and easily accessed by practitioners. In the latter, the solution involves collaboration between academics and practitioners at different key stages of the research process (Pettigrew, 1997). In the papers that follow the nature of the management research–practice gap is debated as well as the helpfulness and viability of various solutions aimed at narrowing it.